Legitimacy and Law in the roman world - A. Meyer, Elizabeth (Cambridge University, 2013)
With typically Roman prudence the emperor [Trajan], by a preliminary test of the trustworthiness of the oracle [of Apollo], took steps to thwart the possibility of hidden human trickery, and began by sending sealed tablets [codicillos] with a request for a written reply. To the surprise of the priests, who were, of course, unaware of the nature of the emperor’s tablets, the god bade a sheet of papyrus [chartam] be brought and ordered it to be sealed, without any writing on it, and dispatched.When Trajan received the document he was filled with astonishment, since the tablets [tabellis] he had sent to the god also had had no writing on them; and he then wrote and sealed other tablets [codicillis], to ask whether he would return to Rome after the war was over. The god thereupon bade a centurion’s vine branch be brought from among the dedicated offerings in the temple, broken in pieces, and the pieces wrapped and sent to the emperor. (Macrobius, Saturnalia 1.23.14–16)